Globalization and Structural Change around the World, 1985–2015 - Wood, Adrian (Published by Oxford University Press on behalf of the World Bank, 2020)
Structural change is a vital element of successful development. Between 1985 and 2015, however, falling barriers to trade and transfer of technology shifted sectoral structures in different directions in different countries by intensifying endowment-related specialization. In skill-abundant developed countries, manufacturing became more skill-intensive and employed fewer workers. In land-scarce developing East Asia, labor-intensive manufacturing expanded, especially and hugely in China. In land-abundant Africa, Latin America, and the Middle East, by contrast, manufacturing shares fell, while in land-scarce South Asia labor-intensive manufacturing was constrained by low literacy and inadequate infrastructure. This pattern of structural change contributed to higher average growth rates during this period in land-scarce than in land-abundant developing countries. Future changes in sectoral structures and growth rates will continue to be shaped by differences among countries in land abundance and skill supplies that matter for development policy choices.